Peran Sikap Keuangan dalam Memediasi Literasi Keuangan Terhadap Perilaku Manajemen Keuangan - Mahendra Galih Prasaja; Endah Pri Ariningsih (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Good financial management is important because it can determine short-term and long-term financial goals. Financial management is also closely related to financial management behavior. Where someone who is able to make decisions in managing their finances will not experience difficulties in the future and will show healthy behavior so that they are able to determine the priority scale regarding their needs and desires. The problem in this research is that the financial management behavior of MSME business actors in Purworejo Regency is still lacking. good at managing their personal finances, the low level of financial literacy of MSMEs in Purworejo, the attitude of MSMEs in Purworejo who tend not to like investing because it is risky. The objectives of this research include (1) testing the influence of financial literacy on the financial management behavior of MSME business actors in Purworejo Regency, (2) testing the influence of financial literacy on the financial attitudes of MSME business actors in Purworejo Regency, (3) testing the influence of financial attitudes on financial management behavior MSME business actors in Purworejo Regency, (4) testing whether financial attitudes are able to mediate the influence of financial literacy on the financial management behavior of MSME business actors in Purworejo Regency. The population in this research is all MSME business actors in Purworejo Regency. The research sample consisted of 150 MSME business actors. Sampling used purposive sampling technique. The data collection instrument used a questionnaire with a Likert scale which was answered completely, in accordance with the criteria and met the validity and reliability requirements